2013
DOI: 10.4067/s0718-33052013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating interactive digital television applications through usability heuristics

Abstract: RESUMENLa Televisión Digital Interactiva (TDi) es considerada como la convergencia de la televisión y las tecnologías de la computación. La evaluación de usabilidad para aplicaciones basadas en tecnologías emergentes trae nuevos retos. La principal característica de la TDi es que los usuarios pueden interactuar con las aplicaciones; de esta manera la usabilidad es el principal aspecto a considerar cuando se diseñan aplicaciones de TDi. Las investigaciones actuales normalmente están enfocadas sobre las aplicaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 6 publications
0
26
0
Order By: Relevance
“…The reported findings from the 17 studies suggest that usability heuristics for specific domains found more usability issues than using existing heuristics that are more general in nature (Berry 2003, Pimentel 2013, Solano et al 2013). However, following further investigation, the results are shown to be inconclusive.…”
Section: Effectiveness Of Usability Heuristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reported findings from the 17 studies suggest that usability heuristics for specific domains found more usability issues than using existing heuristics that are more general in nature (Berry 2003, Pimentel 2013, Solano et al 2013). However, following further investigation, the results are shown to be inconclusive.…”
Section: Effectiveness Of Usability Heuristicsmentioning
confidence: 99%
“…It was found that this was likely caused by evaluators' tendency to ignore them as they were seen to be less problematic in comparison to other issues (Muñoz & Chalegre 2012, Inostroza et al 2012, Neto & Pimentel 2013, Solano et al 2013). There was only three studies reported comparison related to the time taken to perform usability evaluation.…”
Section: Effectiveness Of Usability Heuristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frameworks of usability evaluation, including appropriate methods or combination of methods should be established, in order to get more effective and efficient evaluations on new interaction paradigms. We proposed specific usability heuristics and associated checklists for transactional web applications [20], touchscreen-based mobile applications [21], grid computing applications [22], interactive digital television [23], and virtual worlds [24]. We also developed a cultural -oriented usability heuristics proposal [25].…”
Section: Usability and User Experience Evaluationmentioning
confidence: 99%